Functional hemodynamic testing in pregnancy: recommendations of the International Working Group on Maternal Hemodynamics. (5th February 2018) - Meah, V. L.; Backx, K.; Davenport, M. H.; ,
ABSTRACT: In the general population, functional hemodynamic testing, such as that during submaximal aerobic exercise and isometric handgrip, and the cold pressor test, has long been utilized to unmask abnormalities in cardiovascular function. During pregnancy, functional hemodynamic testing places additional demands on an already stressed maternal cardiovascular system. Dysfunctional responses to such tests in early pregnancy may predict the development of hypertensive disorders that develop later in gestation. For each of the above functional hemodynamic tests, these recommendations provide a description of the test, test protocol and equipment required, and an overview of the current understanding of clinical application during pregnancy. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd. Abstract : This article's abstract has been translated into Spanish and Chinese. Follow the links from theabstract to view the translations.